(untitled) (Fiep Bulletin - online, 2013)
The text is the result of several months of research bibliographic introduction, but of great relevance when we consider this issue in the production physical education course in the Amazon, whose base was in the epistemological foundations sociological discipline in physical education . this is study aims to present and relate sociology of sport associated with the context of football, specifically the city of Santarem, Amazon, Pará whose scant written material incentives to produce this text, based on the memoirs of one of the essays research was based on a theoretical and of interviews. We will make a link between media influence, vision of football as social mobility, transition from amateurism to professionalism, value and relationship with national identity when we focus on the football Santareno and sociology of sport as Conjugated interviewed. It´s, therefore, to discuss relevant issues regarding subject cited before, with a view to elucidate the sociological debate concerning the football in physical education course.